Relationship between perceived physical ability and sport participation motives in young competitive swimmers - Salguero, A.; Gonzalez-Boto, R.; Tuero, C.; Marquez, S. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The purpose of this study was to examine the relationship between participation motives and perceived physical ability in young Spanish swimmers and to investigate whether swimmers with high or low perceived physical competence differ in their intrinsic and/or extrinsic reasons for participation involvement. METHODS: Four hundred and twenty-eight swimmers (204 boys and 224 girls), aged 8-22 years, responded to the Spanish versions of the Participation Motivation Inventory (PMI) and the Perceived Physical Ability Scale (PPA). Swimmers were divided into low (below the 33 %), medium (between the 33-66 %) and high (above the 66 %) perceived ability groups. RESULTS: Multivariate analysis indicated the existence of differences in motives for participation between swimmers with different levels of perceived physical ability. Follow-up univariate analyses yielded significant (p<0.05) effects for 5 motivational factors: health/fitness, fun/friendship, competition/skills, affiliation and status. In all cases swimmers high in perceived physical ability rated significantly higher than those in the other categories. The PPA by gender, age or level of expertise interaction was not significant. CONCLUSIONS: Practitioners must consider the perceived ability of the competitors to better structure the social environment within which their swimmers operate.